1999
DOI: 10.1080/089419399272377
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless and Reduced Suture Anastomosis of Hollow Vessels With Fibrin Glue: A Review

Abstract: Research in reduced suture fibrin glue (FG) and sutureless FG anastomosis has been lagging behind FG utilization in other surgical fields. A review of the literature for vascular, esophageal, tracheal, gastrointestinal, common bile duct, ureteral, vas deferens, and Fallopian tube FG anastomosis indicates that reduced suture FG and sutureless FG procedures may be performed with less training, reduced operating time, leakage, ischemia, inflammation, and necrosis compared to sutured techniques. Reduced suture FG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 117 publications
(223 reference statements)
0
30
0
1
Order By: Relevance
“…Ascheri et al [32] observed that, when compared to the control group, the fibrin sealant group had significantly higher bursting pressures throughout the first 24 hours, whereas they were similar on days 5 and 7. Detweiler et al [33] reported that bursting pressures were significantly lower in the group in which fibrin sealant was used around ileal and colonic anostomoses on day 4. They also reported that fibrin sealant reduced the channel of the anostomosis.…”
Section: Discussionmentioning
confidence: 98%
“…Ascheri et al [32] observed that, when compared to the control group, the fibrin sealant group had significantly higher bursting pressures throughout the first 24 hours, whereas they were similar on days 5 and 7. Detweiler et al [33] reported that bursting pressures were significantly lower in the group in which fibrin sealant was used around ileal and colonic anostomoses on day 4. They also reported that fibrin sealant reduced the channel of the anostomosis.…”
Section: Discussionmentioning
confidence: 98%
“…In the past, fibrin glues have been used to make a sutureless intestine anastomosis and to treat gastrointestinal anastomotic leaks during laparoscopic surgery [30,31].…”
Section: Soft Tissue Healing and Endoscopic Applicationsmentioning
confidence: 99%
“…Reduced operating time, simplicity of use, and lower leakage rates have been proposed as advantages of sutureless fibrin glue procedures [11]. However, although fibrin glue has been successful in constructing various kinds of intestinal anastomoses [12], its use has been associated with reduced blood supply to the anastomosis [11,13], a fact that may affect normal anastomotic healing. As an alternative to fibrin glue, Sweeney et al [13], proposed the use of the biodegradable, hydrogel sealant Focalseal for the construction of sutureless small bowel anastomosis.…”
Section: Discussionmentioning
confidence: 98%
“…The concept of sutureless anastomosis of hollow viscus with the aid of surgical sealants has been investigated in a number of experimental studies, most of which used fibrin glue [11]. Reduced operating time, simplicity of use, and lower leakage rates have been proposed as advantages of sutureless fibrin glue procedures [11].…”
Section: Discussionmentioning
confidence: 99%